2011
DOI: 10.2174/1874325001105010283
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's Disease: Review of the Current Literature

Abstract: Dupuytren’s disease is one of the most common condition seen by hand surgeons. It is not only prevalent but can also be a most debilitating condition resulting in significant loss of function of the fingers involved. The cause of this disease, however still remains largely unknown although some recent evidence suggests a stem cell etiology. This review article summarizes the current known knowledge of Dupuytren’s as well as the clinical findings, investigations and treatments available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 71 publications
0
21
0
2
Order By: Relevance
“…Dermofasciectomy is still a valid treatment option in patients with recurrence or extensive skin involvement 3 . Although fasciectomy and selective fasciectomy are similar in terms of functionality and recurrence rates, complication and morbidity rates are strikingly higher with radical fasciectomy 16 . Khan et al 13 employed regional fasciectomy in 27 of their 30 patients and reported excellent and good results in 97% of the patients after five years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Dermofasciectomy is still a valid treatment option in patients with recurrence or extensive skin involvement 3 . Although fasciectomy and selective fasciectomy are similar in terms of functionality and recurrence rates, complication and morbidity rates are strikingly higher with radical fasciectomy 16 . Khan et al 13 employed regional fasciectomy in 27 of their 30 patients and reported excellent and good results in 97% of the patients after five years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recent review articles reflect both a greater focus on genetics and 1,2 molecular biology [3][4][5][6] and an openness to alternative treatments. [7][8][9][10] …”
Section: Reviewsmentioning
confidence: 99%
“…Main characteristic of the Dupuytren's disease is palmar aponeurosis hyperplasy and contraction which leads to finger flexion contracture [35]. Peyronie's and Dupuytren's diseases have common pathophysiology [36].…”
Section: Pathophysiologymentioning
confidence: 99%